2021
DOI: 10.21203/rs.3.rs-497240/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recurrent hepatic artery thrombosis following living donor liver transplant as sequelae of SARS-CoV-2 infection: case report

Abstract: Background: As the second wave of COVID-19 is gripping the globe, liver transplant centers are increasingly receiving patients with a recent recovery from SARS-CoV-2 infection. Despite full clinical recovery, unexpected, unusual and potentially life-threatening complications in these patients are increasingly being recognized, one such patient is discussed here. By far, this is the first ever reported case of a COVID-19 recovered recipient developing recurrent thrombotic complications, which led us to change o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In general, there have been no obvious COVID-19 related complications in the follow-up of these cases. However, there are reports of portal venous thrombosis and hepatic artery thrombosis in two DDLT transplanted to COVID-19 recovered patients [45,46]. Although the association of this complication with COVID-19 is not clearly delineated, it raises a word of caution.…”
Section: Liver Transplantation After Recovery From Covid-19mentioning
confidence: 99%
“…In general, there have been no obvious COVID-19 related complications in the follow-up of these cases. However, there are reports of portal venous thrombosis and hepatic artery thrombosis in two DDLT transplanted to COVID-19 recovered patients [45,46]. Although the association of this complication with COVID-19 is not clearly delineated, it raises a word of caution.…”
Section: Liver Transplantation After Recovery From Covid-19mentioning
confidence: 99%
“…Several case reports have shown that HAT can happen as a consequence of the infection 11 15. A recurrent form of HAT as a result of COVID-19 was reported in India, which shows the severity of HAT by which the cases might be affected 16…”
Section: Discussionmentioning
confidence: 99%
“…ever since the first studies of COVID-19 were carried out, it was realised that the infection increases coagulopathic incidences such as stroke 13 14. Even though several cases of post-transplantation HAT have been reported, the correlation between the two incidences have not been studied 15 16…”
Section: Introductionmentioning
confidence: 99%
“…Cases of successful liver transplants 2–4 weeks after infection have been anecdotally reported early in the pandemic but are likely to become more frequent given occurrence of reinfections [65]. Some concerns persist regarding hypercoagulable state and risk of arterial thrombosis [66]. When a candidate is found to be positive, serial cycle threshold (Ct) values can be used as a tool to time infection, with Ct values above 32–34 being a marker of low infectivity and potentially lower surgical or complication risk [67].…”
Section: Covid-19 Infected Donors and Recipientsmentioning
confidence: 99%